(untitled) (Indian Journal of Animal Production and Management, 2024)
Rural household-based dairy farming is a crucial component of meeting the national demand for nutrition. Despite the significant contributions women have made to agriculture, particularly in dairy farming, gender discrimination persists in access to resources and services, making it challenging to operate dairy farming effectively. An exploratory qualitative research project was conducted in four different areas of Panchgarh district in Bangladesh to identify the constraints rural women face in dairy farming and gather their suggestions for overcoming them. Data was collected through Focus Group Discussions and analyzed using NVivo v.14, revealing six recurring constraints: high input prices, financial challenges, inadequate marketing facilities, limited training opportunities, inadequate livestock health services, and lack of social support. To address these constraints, women in dairy farming expressed a desire for effective support in financial, marketing facilities, training, livestock health treatment, and community support, which may motivate them to continue farming and even strengthen their entrepreneurship. For this, policymakers must prioritize finding ways to provide work-life balance for rural dairy women to sustain dairy entrepreneurship among them. Both government organizations and non-governmental organizations must also ensure comprehensive financial, institutional, and social support systems. Developing an action plan to address these suggestions and implementing appropriate actions is nothing but a demand of time.